CULTURAL CHARACTERISTICS OF RAMBUTAN PLANT (NEPHELIUM LAPPACEUM L.) THROUGH MORPHOLOGICAL APPROACHES IN ACEH PROVINCE - Najira Jira pv; Mardudi Mardudi; Danu Abian Latfi; Ririn Mustika Ningrum; Ririn Subakti; Isnani Yatul Husna (BIOEDUKASI, 2020)
Rambutan (Nephelium lappaceum L.) is a tropical plant belonging to the lerak-lerakan family or in the Sapindaceae family. The purpose of this study was to obtain a variety of characteristics of Rambutan plants that grow cultivated and wild in Aceh Province. This research was conducted in July - August 2020, the sampling location was carried out in cultivation in the Seruway, Aceh Tamiang and Rambutan areas growing wild in the Jambo Keupok Village Area, South Aceh. The research was conducted using an exploratory method, namely tracing the presence of plants in the research area. Results The morphological characteristics of rambutan are very significant in cultivated and wild rambutan plants in the form of stems. It appears on tree types (round, ovoid and imperfect) on leaves. very significant between leaves and fruit in cultivated plants with average taste (Very sweet, Sweet, Sour, and Very Sour) and in the color of the flesh with a very striking difference in color (transparent and faded, transparent clear and white.